SSCP study guide & DVD training system - Jacobs, Josh. (Rockland, MA : Syngress Pub., 2003)
The SSCP Study Guide and DVD Training System is a unique and comprehensive combination of text, DVD-quality instructor-led training, and Web-based exam simulation and remediation. These components will give the student 100% coverage of all (ISC)² official exam objectives and realistic exam simulation. The SSCP Study Guide and DVD Training System consists of: 1. SSCP Study Guide The 1,000,000 readers who have read previous Syngress Study Guides will find many familiar features in the Study Guide along with many new enhancements including: Exercises: There will be frequent use of step-by-step exercises with many screen captures and line drawings. Exercises will be presented in sidebar-like style, and will run 1 to 2 pages. Anatomy of a Question: Question types will be diagrammed and analyzed to give readers access to the theory behind the questions themselves. Teacher's Pet: These will be written from the instructor's perspective and will provide insight into the teaching methodologies applied to certain objectives that will give readers the "$2,000 worth of training in a $60 book feel." These will be presented in sidebar-like style and will run about 1 page. Objectives Fast Track: End of chapter element containing each A-head from the chapter and succinct bullet points reviewing most important information from each section (same as current Solutions Fast Track). FAQs: End of Chapter Frequently Asked Questions on objective content. These are not exam preparation questions (same as our current FAQ). Test What You Learned: End of chapter exam preparation questions, which are in the format of the real exam. 2. SSCP DVD: The DVD will contain 1 hour of instructor-led training covering the most difficult to comprehend topics on the exam. The instructor's presentation will also include on-screen configurations and networking schematics. SSCP from solutions@syngress.com The accompanying Web site will provide students with realistic exam-simulations software. The exam will emulate the content and the look and feel of the real-exam. Students will be able to grade their performance on the Web-based exam and automatically link to the accompanying e-book for further review of difficult concepts Ά$2,000 worth of training in a $60 book, DVD, and Web-enhanced training system. Consumers of this product will receive an unprecedented value. Instructor-led training for similar certifications averages $2,000 per class, and retail DVD training products are priced from $69 to $129. Consumers are accustomed to paying 20% to 100% more than the cost of this training system for only the DVD! ΆChanges to the CISSP Certification pre-requisites will result in an increase in the popularity of the SSCP certification. Recently the (ISC)² increased the work experience requirement of the CISSP certification to four years from three years. This increase will result into current candidates for the CISSP to shift to the SSCP certification, as the verifiable field requirement is only one year. ΆSyngress well-positioned in wide open playing field. The landscape of certification publishing has changed dramatically over the past month with Coriolis ceasing operations, Hungry Minds facing an uncertain future after their acquisition by John Wiley & Sons, and Syngress ending its long-term relationship with Osborne McGraw Hill in pursuit of publishing Study Guides independently. We are confident that Syngress' long history of best-selling Study Guides will continue in this new era.
1: Overview of the SSCP Certifications -- 2: Access Controls -- 3: Administration -- 4: Auditing & Monitoring -- 5: Risk, Response, and Recovery -- 6: Cryptography -- 7: Data Communications -- 8: Malicious Code.
Includes free web-based testing.
Keywords: Electronic data processing personnel -- Certification; Computer security -- Examinations -- Study guides; Computer networks -- Security measures -- Examinations -- Study guides; Electronic books; Study guides